Clinical trials in Irkutsk Scientific Center of Surgery and Traumatology: results and prospects - K. A. Apartsin; O. V. Demkova; A. V. Gorokhova (Acta Biomedica Scientifica, 2016)
Clinical drug trials in Irkutsk Scientific Center of Surgery and Traumatology began in 2005. In 2013, the laboratory of clinical trials was established in the science department of clinical surgery. We analyzed the experience of Irkutsk Scientific Center of Surgery and Traumatology in international multicentre trials. Participation in international multicentre trials allows the Irkutsk Scientific Center of Surgery and Traumatology to get affiliated with the publications in first quartile scientific journals. The experience of the laboratory in clinical trials is projected into practical work of other institutes - Hospital of Irkutsk Scientific Center SB RAS and Irkutsk Regional Clinical Hospital. The important objectives of the laboratory of clinical trials are developing the protocols, performing drug clinical trials and medical device clinical trials. The laboratory carries out admission of patients for observational trial PROTOCOL. One of the fields of work of the laboratory is the prospect of clinical testing of developed clinical technologies.